Evaluation of Reproductive Performance of Bali Cattle on Semi-Intensive in Field Station of School for smallholder community (SL-SPR) Sungai Lilin, Musi Banyuasin District, South Sumatera - Z. Abidin; Muladno; A. Gunawan (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
Empowering smallholder cattle farmers through the Field station of School for Smallholder Community (SL-SPR) Program is one of the efforts to improve the reproductive performance of Bali cattle in smallholder farmers. This research aims to evaluate the reproductive performance of Bali cattle reared semi-intensively in SL-SPR Sungai Lilin, South Sumatra. Data on reproductive performance were collected from the observation method through direct observation and interviews with respondents in the community. The respondents was totally 45 smallholder farmers, with a total number of Bali cattle observed of as many as 150 cattle and 372 heads of cow-calf. The data were analyzed using descriptive analysis of variance mixed model using SAS 9.2 software. The results showed that Bali cattle reproductive performances average first calving (AFC) was 971.09 ± 246.47 days. The average calving interval (CI) value was 381.90±72.33 days, while the average days open (DO) value was 111.90±72.33 days. However, the values of AFC, CI and DO had no significant differences (P>0.05) based on differences in season, sex, year of birth, and the interaction between the year of birth, and parity. Bali cattle reproductive performance in SL-SPR Sungai Lilin is in the ideal category.